Hardware Commissioning of the Refurbished ALPI Linac at INFN-LNL to Serve as SPES Exotic Beam Accelerator. (November 2019) - Bisoffi, G; Bellan, L; Bellato, M; Borille, D; Bortolato, D; Carletto, O; Chiurlotto, F; Comunian, M; Conte, A; Contran, T; De Lazzari, M; Fagotti, E; et al.
Abstract: The ALPI linac at INFN-LNL was substantially refurbished in 2018, especially in view of its use as secondary accelerator for exotic species in the framework of the SPES project. In particular: 10 magnetic triplets were replaced with higher gradient ones; two cryomodules with quarter wave resonator were moved from the PIAVE injector to ALPI, so as to make them available both for exotic and stable beams; the cryogenic plant was renovated; the whole linac, its injector and its beam lines were eventually realigned via LASER tracking (LT). The expected outcome of the refurbishment project is a larger beam transmission (crucial for the efficient transport of the unavoidably low current exotic beams) and improved overall reliability so as to further extend the lifetime of an already 25 years old machine. The hardware commissioning of this new configuration will be reported.